An Econometric Analysis of U.S. Foreign Direct Investment - Barrell, Ray; Pain, Nigel (The Review of Economics and Statistics, 1996)
This paper constructs a theoretical model of foreign direct investment and examines the extent to which the model can explain the level of outward direct investment by U.S. companies over the last two decades. The authors find that market size and factor costs, both labor and capital, are important factors in the investment decision. Instrumental variable estimation is used to demonstrate that the expectation of short-run fluctuations in the dollar also influences the timing of investment. Copyright 1996 by MIT Press.